Revitalizing faith: an inquiry into political Sufism and religious continuity in contemporary Kazakhstan - Karimov, Nodar; Karimova, Risalat-Bibi; Massimova, Khalminyam; Khajiyeva, Gulzhakhan (Frontiers in Sociology, 2024)
The article embarks upon a study of political Sufism in contemporary Kazakhstan and patterns of religious continuity through an examination of Islamic manifestations that stretch back centuries, juxtaposed with the current state religious policy. It examines the role of the Muftiate’s “official Islam” in shaping the life of religious communities, exploring the intricate interplay between religious identity, secularism, and public perception in the post-Soviet landscape. The author employed a multi-faceted research approach, integrating historical analysis, policy examination, and an ethnographic study of contemporary religious dynamics in the country. The historical analysis provides a foundation of the religious landscape, while policy analysis examines the state’s contemporary role in shaping religious practices. Ethnography, focusing on groups such as the Jahriyya, Naqshbandiyya, and the Suhba, involves respondents from diverse regions of Kazakhstan, offering firsthand insights into the experiences and perceptions of Sufi communities at the grassroots level, which enriches the study with a contextual perspective. Notably, fieldwork surveys, where the author engaged with respondents, provide valuable insights into the diverse experiences shaping the dynamics of political Sufism and religious continuity. They involved a diverse group of respondents, including religious leaders, community members, and secular intellectuals, from multiple regions of Kazakhstan at both urban and rural levels. The article is of scientific and practical significance as it enhances understanding of religious dynamics in the country, offering policymakers, scholars, and practitioners valuable perspectives for informed decision-making and policy development. The research’s limitations include its focus on specific Sufi groups within Kazakhstan, which may not represent the full spectrum of Islamic practices across the region. The recommendations emphasize the need for further analysis of how prioritizing doctrinal adherence over individual freedoms contributes to the erosion of authentic religious institutions and the politicization of Islam. It also recommends to investigate the roles of Sufi groups in filling spiritual and social vacuums, their potential for politicization, and how this interplay affects religious freedom and national identity in Kazakhstan. This is particularly significant given the state’s efforts to appropriate Islamic traditions for ideological purposes, which has led to a separation between Islamic doctrine and its lived expressions. Finally, it emphasizes the need for further comparative research on Sufi movements across Central Asia to better understand how different state policies impact religious communities.